Foreign direct investor’s satisfaction for the tax support service in Vietnam - Van, Nguyen Thi (International Journal of Advanced Science and Technology, 2020)
This research aims to investigate the service quality of tax support in the view of FDI (foreign direct investment) companies in Vietnam. Data was collected from 222 FDI companies in Ho Chi Minh City, Binh Duong, and Dong Nai, Vietnam. The proposed research model was based on researches on service quality. Cronbach's Alpha, Average Variance Extracted (Pvc), and Composite Reliability (Pc) tested the reliability and validity of the scale. The analysis results showed that four factors were affecting the service quality of tax support in Vietnam being tangibles, reliability, the empathy of FDI investors, and assurance. The responsiveness did not affect the service quality of tax support. Contents of the article focus on two main issues: the analysis framework of the quantitative model and implicating results to develop the tax support services.